Cost variation analysis of antihypertensive drugs acting through renin angiotensin aldosterone axis modulation - Nair, Manju K.; S., Neha M. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Several brands of antihypertensive drugs are available in the Indian market with huge price variations. This study was undertaken to find out the percentage cost variation and cost ratio of antihypertensive drugs acting through renin angiotensin aldosterone axis modulation. Methods: Costs of different brands of renin angiotensin aldosterone axis modulatory drugs with antihypertensive action for the same dosage form and strength were found out using current index of medical specialties-134, July-October 2016. The maximum and minimum price of different brands of each drug was noted. Data was entered in Microsoft excel 2010. Percentage cost variation and cost ratio was calculated for each drug. Results: 16 antihypertensive drugs were analysed. Most of them were tablets. Ramipril and Valsartan were available as capsules also. Among tablets, percentage cost variation was highest for Atenolol 12.5 mg (683.93%) and least for Bisoprolol 2.5 mg (3.6538%). Valsartan capsules (160 mg) had no difference in the costs between the available 2 brands. Cost ratio ranged from 1.04 to 7.84 among the tablet form of drugs. Conclusions: There is a huge difference in the cost of antihypertensive drugs manufactured by different companies in the same strength and dosage form. To promote rational drug use and cost effective therapy, it is essential to create an awareness among clinicians regarding the availability of multiple brands for these drugs and the discrepancies in their costs.